EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF MISSOURI MATHEMATICS PROJECT (MMP) DAN THINK PAIR SHARE (TPS) DENGAN PENDEKATAN SAINTIFIK PADA MATERI PERSAMAAN GARIS LURUS DITINJAU DARI KECERDASAN EMOSIONAL SISWA SMP NEGERI SE-KABUPATEN PEMALANG - Adeyanto, Rizki; Kusmayadi, Tri Atmojo; Riyadi, Riyadi (Universitas Sebelas Maret, 2016)
Abstract: The aim of the research was to determine the effect of learning models scientific MMP, scientific TPS, scientific classical on mathematics achievement viewed from student Emotional Quotient (EQ). The objectives of research were to find out: 1) which one providing better learning achievement, scientific MMP, scientific TPS, or scientific classical. 2) which one having better learning achievement, students with high, medium, or low EQ. 3) in each learning models, which one having better learning achievement, students with high, medium, or low EQ. 4) in each EQ level, which one providing better learning achievement, scientific MMP, scientific TPS, or scientific classical. The type of the research was quasi experimental research using design factorial 3x3. The population was the students in grade VIII junior high school in a city of Pemalang. The size of the sample was 309 students. The hypothesis test used unbalance two ways analysis of variance. The conclusions of the research were as follows. 1) Scientific MMP provided better learning achievement than scientific TPS and scientific classical, while scientific TPS provided better learning achievement than scientific classical. 2) The students with high EQ had better learning achievement than medium and low EQ, while the students with medium EQ had better learning achievement than low EQ. 3) In scientific MMP, scientific TPS, scientific classical, the students with high EQ had better learning achievement than medium and low EQ, while the students with medium EQ had better learning achievement than low EQ. 4) At the students with high, medium, and low EQ, Scientific MMP provided better learning achievement than scientific TPS and scientific classical, while scientific TPS provided better learning achievement than scientific classical.Keywords: scientific MMP, scientific TPS, scientific Classical, Emotional Quotient,n Achievement